Sensor Design Optimization of Innovative Low-Power, Large Area FD-MAPS for HEP and Applied Science - Neubüser, Coralie; Corradino, T.; Dalla Betta, G-F.; De Cilladi, L.; Pancheri, L. (Frontiers in Physics, 2021)
Fully depleted monolithic active pixel sensors (FD-MAPSs) represent a state-of-the-art detector technology and profit from a low material budget and cost for high-energy physics experiments and other fields of research like medical imaging and astro-particle physics. Compared to the MAPS currently in use, fully depleted pixel sensors have the advantage of charge collection by drift, which enables a fast and uniform response overall to the pixel matrix. The functionality of these devices has been shown in previous proof-of-concept productions. In this article, we describe the optimization of the test pixel designs that will be implemented in the first engineering run of the demonstrator chip of the ARCADIA project. These optimization procedures include radiation damage models that have been employed in Technology Computer Aided Design simulations to predict the sensors’ behavior in different working environments.